Aplasia cutis congenita with dystrophic epidermolysis bullosa: clinical and mutational study. (1st April 2014) - Chiaverini, C.; Charlesworth, A.; Fernandez, A.; Barbarot, S.; Bessis, D.; Bodemer, C.; Bursztejn, A.‐C.; Cobo, A.‐M.; Del Rio, M.; D'Incan, M.; Labrèze, C.; Langlet, C.; et al.
Summary: Background: Aplasia cutis congenita (ACC) has been associated with all clinical forms of inherited epidermolysis bullosa (EB), including dominant and recessive dystrophic EB (DDEB and RDEB). To date, only a few patients with DEB specifically combined with ACC have been described and genotyped and almost all cases represent dominant forms of the condition. Objectives: The aim of this study was to describe new mutations of COL7A1 in patients with DEB and ACC and investigate possible genotype–phenotype correlations. Methods: Twenty‐two patients with DEB and ACC were included among the 123 patients with DEB whose COL7A1 mutations have been identified in the Reference Centre in Nice. Results: Seven patients presented a severe generalized RDEB phenotype (RDEB‐sev‐gen), while the other 15 suffered from milder phenotypes. We identified 28 mutations in COL7A1, of which nine are novel. Patients with severe phenotypes have mostly mutations leading to premature termination codon (PTC) and/or splice‐site or missense mutations. Patients with the milder phenotypes have mostly glycine or arginine substitutions associated or not with other types of mutations. All amino acid substitutions fell within the carboxyl portion of the triple helix domain (THD) of collagen VII, close to the THD interruptions. Conclusions: Our findings suggest that ACC is a frequent manifestation in patients with DEB irrespective of the severity of the disease, and is due to leg rubbing in utero . In children with a moderate form of DEB with no or moderate skin fragility, a glycine substitution near the THD interruption domain of the collagen VII leading to thermolabile protein could explain this phenomenon.